2019
DOI: 10.15381/rivep.v30i1.15665
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia de piometra en perras pacientes de la Clínica de Animales Menores de la Facultad de Medicina Veterinaria de la Universidad Nacional Mayor de San Marcos durante el periodo 2009-2013

Abstract: Se revisaron las fichas clínicas de perras mayores de seis meses que fueron atendidas en la Clínica de Animales Menores de la Facultad de Medicina Veterinaria de la Universidad Nacional Mayor de San Marcos durante el periodo 2009-2013, con el fin de obtener información estadística acerca de la frecuencia de piometra y su relación con la edad, raza, tamaño y estación del año. De los 4715 registros de perras, 207 fueron diagnosticados con piometra, representando un 4.4 ± 0.6% de incidencia. Se halló asociación e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The age range between 5 and 10 years was the one that presented the highest (p<0.05) occurrence of pyometra in the animals of the study. This observation suggests that the prevalence of pyometra in animals in this age group increases as a result of changes due to chronic and repetitive exposure of the uterus to progesterone during the estrous phase (Gibson et al, 2013;Hagman, 2018;Kumar & Saxena, 2018;Solano et al, 2019). Moreover, it was identified that the second group with the highest occurrence was animals under five years of age (young animals), showing that pyometra can also affect young animals, and that it is probably associated with an abnormal response of the uterus to a prolonged phase of exposure to progesterone instead of repetitive exposures, as it occurs in older bitches (Hagman, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age range between 5 and 10 years was the one that presented the highest (p<0.05) occurrence of pyometra in the animals of the study. This observation suggests that the prevalence of pyometra in animals in this age group increases as a result of changes due to chronic and repetitive exposure of the uterus to progesterone during the estrous phase (Gibson et al, 2013;Hagman, 2018;Kumar & Saxena, 2018;Solano et al, 2019). Moreover, it was identified that the second group with the highest occurrence was animals under five years of age (young animals), showing that pyometra can also affect young animals, and that it is probably associated with an abnormal response of the uterus to a prolonged phase of exposure to progesterone instead of repetitive exposures, as it occurs in older bitches (Hagman, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among the clinical signs identified, three presented higher prevalence (p<0.05), being apathy (94.4%), anorexia/hyporexia (90.1%) and vaginal discharge (83%), evidencing these as the most common symptoms in patients diagnosed with pyometra, especially for being characteristic signs of open pyometra (Hagman et al, 2011;Jitpen et al, 2016;Dyba et al, 2018;Oliveira et al, 2019;Solano et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that some bacteria, more specifically the enterobacteria E. coli, are often responsible for the emergence of pyometra in bitches, usually inhabiting the vagina, urinary tract, and intestinal tract of the animals [28,29]. They are also responsible for bacterial infections of the genitourinary tract affecting approximately 10 to 14% of male dogs [30][31][32]. Works focus on the identification and required use of antimicrobials only after the results of the phenotypic tests of susceptibility to these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Se evaluaron las variables sexo, raza y edad. La edad se dividió en cinco categorías: <1, 1-4, 5-8, 9-12 y >12 años (Solano, 2017). La frecuencia de los agentes bacterianos y los patrones de sensibilidad antibiótica fue establecida mediante la fórmula: Ni (total de valores d» X 1 )/N (total de datos: X 1 , X 2 ,…X n ) x 100.…”
Section: Materiales Y Métodosunclassified